2003
DOI: 10.1111/1532-7795.1302002
|View full text |Cite
|
Sign up to set email alerts
|

Friendship Quality, Peer Group Affiliation, and Peer Antisocial Behavior as Moderators of the Link Between Negative Parenting and Adolescent Externalizing Behavior

Abstract: Quality of peer relationships and perceived peer antisocial behavior were examined as moderators of the link between negative parenting and externalizing behavior problems in school from middle childhood to early adolescence. Data on negative parenting (i.e., unilateral parental decision making, low supervision and awareness, and harsh discipline) were collected from 362 parents in the summer preceding the adolescents' entry into Grade 6. Adolescent reports of positive peer relationships and peer antisocial be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
142
1
11

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 200 publications
(173 citation statements)
references
References 59 publications
19
142
1
11
Order By: Relevance
“…In some cases, the quality of peer relationships can attenuate or exacerbate the ill effects of family characteristics on adolescent outcomes (Lansford, Criss, Pettit, Dodge, & Bates, 2003 ). In other cases, family functioning serves to moderate associations between peer experiences and adolescent adjustment.…”
Section: Family Influencesmentioning
confidence: 99%
“…In some cases, the quality of peer relationships can attenuate or exacerbate the ill effects of family characteristics on adolescent outcomes (Lansford, Criss, Pettit, Dodge, & Bates, 2003 ). In other cases, family functioning serves to moderate associations between peer experiences and adolescent adjustment.…”
Section: Family Influencesmentioning
confidence: 99%
“…Parenting behaviors are also important examples of protective and vulnerability factors. These include positive parenting and parental monitoring (Patterson, Reid, & Dishion, 1992), which appear to be protective factors, and physical discipline (Gershoff, 2002) and unilateral parental decision making during adolescence (Lansford, Criss, Pettit, Dodge, & Bates, 2003), which seem more likely to be vulnerability factors.…”
Section: Protective and Vulnerability Factorsmentioning
confidence: 99%
“…Parents rated 16 items on a 4-point scale (1 = child decides, 2 = joint decision, 3 = discuss but parent has final say, 4 = parent decides; Lansford et al, 2003). Items were averaged to create the final unilateral parental decision making score (α = .72).…”
Section: Procedures and Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The data, however, are also consistent with the notion that coercive peer interactions reflect a degree of reciprocity (e.g. Snyder, 1992), as well as research that has found that peers who engage in antisocial behaviors contribute to their friend's high levels of aggression through lack of appropriate social skills training, deviancy training, and exposure to aggressive social encounters (c.f., Capaldi, Dishion, Stoolmiller, & Yoerger, 2001;Lansford, Criss, Pettit, Dodge, & Bates, 2003;Snyder, 1992). That is, the child reports of peer's harsh reactions could reflect assortative friendships, with children who are physically aggressive establishing friendships with other children who are also physically aggressive, which can then lead to rejection from non-aggressive peers.…”
Section: Discussionmentioning
confidence: 99%